Impacts of flooding on rural communities in Bangladesh - Sumana Akter (Journal of Fisheries, 2024)
Flooding is a regular phenomenon in many countries, including Bangladesh, causing severe damage to communities. Despite widespread impacts, most studies focus on a single community. This study examines the impacts of flooding on three key rural Bangladeshi communities: agriculture farmers, fish farmers, and fishermen. Data were collected from three flood-prone areas: Roumari Upazila (Kurigram district), Chauhali Upazila (Sirajganj district), and Char Bhadrasan Upazila (Faridpur district). The mean age of respondents varied across groups (LMM: F = 21.2, p < 0.001), but not across study sites. The mean education level was 6.9 ± 4.9 years, with fish farmers having the highest schooling at 7.4 years. Monthly income varied across groups (LMM: F = 174.3, p < 0.05). Most respondents (84.7%) received financial loans from non-government sources. Flooding negatively affected agricultural and fish farmers, who lost their crops. However, fishermen experienced a positive effect, with increased fishing days and duration, leading to higher fish harvests during floods  (LMM: all p < 0.05). The study also highlights respondents’ expectations to minimize flood impacts. The findings of this study are crucial for understanding the variation in flood impacts on key communities in rural Bangladesh and can inform effective flood management planning.